2004
DOI: 10.1016/j.ejcts.2004.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Microwave and radiofrequency ablation yield similar success rates for treatment of chronic atrial fibrillation1

Abstract: The combination of complex valve surgery and Maze procedure was safe and reproducible. Following the Cox Maze III line concept, microwave and radiofrequency ablation gave similar results even in patients with more complex double or triple valve procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…The basic concept has been widely received. Major modifications have supplanted the traditional 'cut-and-sew' with cryoablation [8,18,20], microwave [13] and radiofrequency [6,14], or mini-maze [16,17] and radial maze [15], with the continued goal of durable results in maintaining optimal cardiac function under sinus rhythm by rapid and safe surgical interventions. In this series of patients, we mainly used three kinds of maze procedures in 13 years; Cox-maze III, Kosakai maze and cryo-maze.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic concept has been widely received. Major modifications have supplanted the traditional 'cut-and-sew' with cryoablation [8,18,20], microwave [13] and radiofrequency [6,14], or mini-maze [16,17] and radial maze [15], with the continued goal of durable results in maintaining optimal cardiac function under sinus rhythm by rapid and safe surgical interventions. In this series of patients, we mainly used three kinds of maze procedures in 13 years; Cox-maze III, Kosakai maze and cryo-maze.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have reported that combining maze procedure with mitral valve surgery has advantages with regard to survival [8], cardiac function [9,10], and stroke incidence [11,12]. At the same time, various modifications over the past decade have improved and refined the maze procedure [6,[12][13][14][15][16][17][18][19][20][21]. This has enabled surgeons to perform maze procedures rapidly and safely.…”
Section: Introductionmentioning
confidence: 99%
“…The cure rate at 1 year has remained at over 90% [27]. Other authors have used different energy sources with similar results [29][30][31][32][33]. The full lesion set can be performed through a right minithoracotomy, and can be achieved for any of the ablation devices.…”
Section: Opinion Statementmentioning
confidence: 95%
“…In a prospective randomized trial, Schuetz and colleagues [38] used a combination of microwave ablation and atrial size reduction to restore sinus rhythm in 80% of patients presenting with permanent atrial fibrillation. In another study, microwave and unipolar radiofrequency produced equivalent results (80% freedom from AF at 1 year) when used to create the Cox-Maze III lesion set [39]. …”
Section: Surgical Treatment Optionsmentioning
confidence: 99%